2000
DOI: 10.1530/eje.0.1430585
|View full text |Cite
|
Sign up to set email alerts
|

Use of human GH in elderly patients with accidental hip fracture

Abstract: Objective: To investigate whether early intervention with recombinant human growth hormone (hGH) after hip fracture improves functional recovery and long-term outcome. Subjects and methods: Functional recovery after hip fracture is often incomplete. The catabolic situation that develops after the hip fracture accident, and a state of malnutrition either pre-existing or developing after surgery, are main contributing factors for the poor clinical outcome. hGH has been used to promote anabolism in a variety of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…The age-related reduction in energy intake has been termed "the anorexia of aging" and predisposes to the development of under-nutrition, which has been implicated in the development and progression of chronic diseases commonly affecting the elderly, as well as in increasing mortality. Growth hormone therapy increases IGF-I levels, promotes anabolism and increases muscle strength in healthy elderly individuals, as well as in selected patient groups [48][49][50]. Therefore, ghrelin and GHS may also have therapeutic potential to assist in the recovery of frail patients who require nutritional support and conventional rehabilitation [51].…”
Section: Gh Deficiency-related Disordersmentioning
confidence: 99%
“…The age-related reduction in energy intake has been termed "the anorexia of aging" and predisposes to the development of under-nutrition, which has been implicated in the development and progression of chronic diseases commonly affecting the elderly, as well as in increasing mortality. Growth hormone therapy increases IGF-I levels, promotes anabolism and increases muscle strength in healthy elderly individuals, as well as in selected patient groups [48][49][50]. Therefore, ghrelin and GHS may also have therapeutic potential to assist in the recovery of frail patients who require nutritional support and conventional rehabilitation [51].…”
Section: Gh Deficiency-related Disordersmentioning
confidence: 99%
“…In a 2-year study in elderly women with low bone mass using cyclical rhGH, bone density increased in the spine by 3%, and lesser changes were found in the hip [62]. In elderly women over 75 years of age with a recent hip fracture, a 6-week treatment with rhGH significantly increased the chance of returning to their pre-fracture living situation, but no effect was found below 75 years of age [63]. …”
Section: Gh Therapy In Osteoporosismentioning
confidence: 99%
“…This was observed during both intramembranous bone formation and during secondary fracture healing, where bone formation is predominantly achieved by endochondral ossification (7)(8)(9)39 A previous study reported a very moderate effect in recovery of elderly patients with hip fractures receiving GH treatment, and this moderate effect might be ascribed to the short treatment duration (6 weeks) and the relatively low GH dose (i.e. 20 mg/kg per day) administered (1). In the present study, no significant enhancement of fracture healing effect was observed in open or closed fractures with 15 or 30 mg/kg, although an increase was observed at these dose levels with regard to levels of IGF-I and markers of bone remodelling.…”
Section: Discussionmentioning
confidence: 99%